If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -7y)(x + 3y) = 0 Multiply (3x + -7y) * (x + 3y) (3x * (x + 3y) + -7y * (x + 3y)) = 0 ((x * 3x + 3y * 3x) + -7y * (x + 3y)) = 0 Reorder the terms: ((9xy + 3x2) + -7y * (x + 3y)) = 0 ((9xy + 3x2) + -7y * (x + 3y)) = 0 (9xy + 3x2 + (x * -7y + 3y * -7y)) = 0 (9xy + 3x2 + (-7xy + -21y2)) = 0 Reorder the terms: (9xy + -7xy + 3x2 + -21y2) = 0 Combine like terms: 9xy + -7xy = 2xy (2xy + 3x2 + -21y2) = 0 Solving 2xy + 3x2 + -21y2 = 0 Solving for variable 'x'. Factor a trinomial. (3x + -7y)(x + 3y) = 0Subproblem 1
Set the factor '(3x + -7y)' equal to zero and attempt to solve: Simplifying 3x + -7y = 0 Solving 3x + -7y = 0 Move all terms containing x to the left, all other terms to the right. Add '7y' to each side of the equation. 3x + -7y + 7y = 0 + 7y Combine like terms: -7y + 7y = 0 3x + 0 = 0 + 7y 3x = 0 + 7y Remove the zero: 3x = 7y Divide each side by '3'. x = 2.333333333y Simplifying x = 2.333333333ySubproblem 2
Set the factor '(x + 3y)' equal to zero and attempt to solve: Simplifying x + 3y = 0 Solving x + 3y = 0 Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. x + 3y + -3y = 0 + -3y Combine like terms: 3y + -3y = 0 x + 0 = 0 + -3y x = 0 + -3y Remove the zero: x = -3y Simplifying x = -3ySolution
x = {2.333333333y, -3y}
| 5x-3x-10=-34 | | 3x-8=-5x-20 | | -(v+4)=-4-3v | | -9+k+3k=9-2k | | 14x-21=12x+29 | | 3x+2(x+10)=170 | | N*(2n-4)=17 | | 28x+52=25 | | 3x^2+2x^2=0 | | 2(v+8)=8(-v-8) | | 5+7x=96 | | 7a+2=1 | | 1.5-.4y=3.3 | | 6x^2-44x=-63 | | -(7v+7)=5-4v | | Q+83=902 | | p=6+7p | | -38=2(-43d-24) | | 9c-6-6c=16 | | 4(y+1)=6y-8 | | -10-3h=8h+3+9 | | (4m-120)= | | -8(r-6)=-8-6(-2+5r) | | -13m+7m=18-66 | | 8.7x=156.6 | | 5x-(3x-2)=18 | | -8x-8=3x+25 | | -8-5(1+6x)=5(1-6x)2x | | -3+a/4=-4 | | V+4-8=6(v+7)+2(v+5) | | 8(x-7)=-112 | | -12-11d=-10d |